Alcohol Consumption and Risk for Venous Thromboembolism: A Meta-Analysis of Prospective Studies - Chen, Mengyan; Ji, Mingxia; Chen, Tiejiang; Hong, Xiaofei; Jia, Yian (Frontiers in Nutrition, 2020)
The association between alcohol consumption and venous thromboembolism (VTE) risk has been investigated by various observational studies with inconsistent results. We examined this association by performing a meta-analysis of prospective studies. A comprehensive literature search was carried out in the PubMed, EMBASE, and Web of Science from its inception to February 2020. Pooled effect estimates were calculated using a random effect model. Ten prospective studies (14 cohorts) were included in this meta-analysis with a total of 441,128 individuals and 10,221 VTE cases. Overall, the highest consumption of alcohol was not associated with the VTE risk compared with the lowest group (RR: 0.96 [95% CI 0.89-1.04], P = 0.293). No obvious heterogeneity of RRs was observed across these studies (P = 0.249 for heterogeneity, I2 = 18.8 %). Egger’s and Begg’s tests showed no evidence of publication bias (Egger, P = 0.443; Begg, P = 0.730). In the subgroup analysis by sex, a borderline significant association between alcohol consumption and VTE risk was observed in women (RR: 0.91 [95% CI 0.82-1.00]). In the dose-response analysis, we observed a linear decrease in VTE risk with increasing alcohol intake (P = 0.634 for non-linearity). However, the reduced risk was not statistically significant. In conclusion, the results from this meta-analysis suggest that alcohol intake is not related with the risk of VTE. Further large well-designed cohort studies are warranted to investigate a potential protective role of alcohol against VTE in women.